2013
DOI: 10.7785/tcrt.2012.500333
|View full text |Cite
|
Sign up to set email alerts
|

Drug Embedded PVP Coated Magnetic Nanoparticles for Targeted Killing of Breast Cancer Cells

Abstract: Magnetic drug targeting is a drug delivery system that can be used in loco-regional cancer treatment. Coated magnetic particles, called carriers, are very useful for delivering chemo- The present findings showed that Epirubicin hydrochloride loaded PVP coated iron oxide nanoparticles are promising for magnetically targeted drug delivery. The drug displayed increased cell cytotoxicity at lower concentrations when conjugated with the nanoparticles than being administered conventionally as individual drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 20 publications
1
19
0
Order By: Relevance
“…From the results, the UV-Vis spectrum analysis confirmed that the drug loading efficiency to the PVP coated iron oxide nanoparticles with the methanolic extract of the Syzygium aromaticum showed more efficiency. Similar types of results were observed using different plant extracts respectively [24,25]. So, these results were correlated with previous observations.…”
Section: Uv-visible Spectroscopysupporting
confidence: 91%
“…From the results, the UV-Vis spectrum analysis confirmed that the drug loading efficiency to the PVP coated iron oxide nanoparticles with the methanolic extract of the Syzygium aromaticum showed more efficiency. Similar types of results were observed using different plant extracts respectively [24,25]. So, these results were correlated with previous observations.…”
Section: Uv-visible Spectroscopysupporting
confidence: 91%
“…The latter is further polymer functionalized on the basis of previously prepared IONPs. Todate, dextran, chitosan, alginate, polyethylene glycol (PEG), polyvinyl alcohol (PVA), polydopamine (PDA), polysaccharide, polyethylenimine, polyvinylpyrrolidone (PVP), poly acid polyetherimide, and polyamidoamine (PAMAM) are the most commonly used polymers for the surface modification of IONPs ( Table 3 ) [ 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 ].…”
Section: Surface Modification Of Magnetic Iron Oxide Nanoparticlesmentioning
confidence: 99%
“…Up to now, PVP has been used in the pharmaceutical and biomedical fields to develop different drug delivery systems, such as oral, topical, transdermal, and ocular administration. Besides, PVP is also useful in the delivery of genes [8][9][10][11][12] or can be coupled with metal particles for regenerative medicine [13][14][15] and targeted-delivery [16,17]. Therefore, PVP results to also be a very versatile polymer.…”
Section: Introductionmentioning
confidence: 99%